Cholinergic neuron‐like D‐U87 cells promote polarization of allergic rhinitis T‐helper 2 cells. Issue 2 (28th October 2019) - Liu, Honghui; Wang, Tiansheng; Xia, Jinye; Ai, Jingang; Li, Wei; Song, Yexun; Shen, Yang; Zhang, Xiaowei; Tan, Guolin
Abstract : Background: Parasympathetic nerve hypersensitivity contributes to the severity of allergic rhinitis (AR), but the precise mechanism underlying neuroimmune regulation in patients with AR remains unclear. This study investigated the effect of cholinergic nerve inhibition on AR CD4 + T‐helper (Th)2‐cell polarization and the underlying regulatory mechanism in vitro. Methods: An in‐vitro neuroimmune coculture model of D‐U87 cells and CD4 + T cells was established. D‐U87 cells with cholinergic neuron characteristics were used as cholinergic neuron models. CD4 + T cells were derived from peripheral blood monocytes from AR patients (n = 60) and control subjects (n = 40). Th1‐ and Th2‐cell percentages were measured by flow cytometry. Proteins involved in related signaling pathways were analyzed by protein chip assay and Western blotting. Results: The Th2‐cell percentage among CD4 + T cells from AR patients was significantly increased after coculture with D‐U87 cells and was decreased by ipratropium bromide (IB) treatment. In contrast, the Th1‐cell percentage among control CD4 + T cells was significantly increased after coculture with D‐U87 cells, but was unaltered by IB treatment. Furthermore, phosphorylated Akt (p‐Akt) protein levels increased in CD4 + T cells from both controls and AR patients after coculture with D‐U87 cells and decreased after IB treatment. However, higher p‐Akt levels were observed in cells from AR patients than in cells from control subjects. Moreover, Akt inhibition decreased Th2‐cell percentage in AR patients. Conclusion: In‐vitro cholinergic nerve inhibition with IB decreased AR CD4 + T‐cell polarization into Th2 cells partially through an Akt‐dependent mechanism.